Effect of chemically pretreated paper mill sludge ash on the properties of geopolymer mortar - Nabilah, Mamat (2021)
Geopolymer has been well known as a sustainable alternative binder to ordinary Portland cement (OPC) because of it properties such as high compressive strength, good chemical and thermal resistance and low toxic composition. In geopolymer, utilization of fly ash as the main aluminosilicate source has been widely used due to high amount of silica (SiO2) and alumina (Al2O3). However, abundant of industrial waste are being released from various industries has become difficulties in their disposal and will affect to the environment. Therefore, it is possible to use different types of wastes such as paper mill sludge ash (PMSA) mixed with fly ash as raw materials. This combination would help to provide better or comparable strength and durability properties and also help in reducing the percentages of waste by product. However, this waste cannot be used alone in the geopolymer because of insufficient amount of SiO2 and Al2O3 and high amount of Ca. The present of high amount of Ca in geopolmyer contributed to the rapid setting time and low workability. Therefore, this study was proposed to treat the paper mill sludge ash and investigate the effect of pretreated PMSA in geopolymer mortar at various curing temperature (30°C and 90°C). PMSA has been treated with hydrochloric acid (HCl) at various molarities which is 0.5 M, 1.0 M and 1.5 M. A series of test were conducted to determine the properties of geopolymer containing pretreated PMSA at various percentages of 5%, 10% and 15% by weight of fly ash. Flowability and setting time test were conducted to determine the rheological properties while compressive strength, porosity and degree of reaction tests were conducted to determine the mechanical properties. Meanwhile, XRF and XRD were tested on raw materials of fly ash, PMSA and pretreated PMSA to ascertain the oxide composition and crystalline material. Inductively coupled plasma mass spectrometry (ICPMS) was tested on solution of pretreatment PMSA to determine the heavy metal concentration. Meanwhile, Fourier Transform Infrared Spectroscopy (FTIR) testing was conducted to identify chemical bonds. Based on the experimental results, by treated PMSA in acid washing using HCl has significantly enhanced the oxide percentages such as SiO2 (8.23% to 44.00%) and Al2O3 (4.36% to 19.60%) and reduce the amount of CaO (52.61% to 22.00%). High amount of SiO2and Al2O3 have a major role to play in the geopolymer backbone formation (Si–O–Al and Si–O–Si bonds). Meanwhile, addition percentages of CaO in aluminosilicate source have produced the secondary product which is CSH gel in geopolymer matrix as Ca–O bond is more susceptible to break the bonds than Al–O and Si–O. Each oxide composition is also functioning in the production of final structure by controlling the geopolymer gel and crystal growth hence contribute to the structural development. The optimum percentages inclusion of pretreated PMSA in geopolymer was 5% with 1.5 M of HCl. This combination has significantly prolonged the setting time, high workability, higher in compressive strength, reduce the porosity and produce denser microstructure. Exposure to 90 °C of curing temperature has accelerated the geopolymerization process and enhances the formation of geopolymer gel in geopolymer framework. Conclusively, the use of pretreated PMSA in geopolymer would reduce quantity of wastes thrown at landfill and promote the development of construction materials contributing towards cleaner environment for healthier community.